2004
DOI: 10.1161/01.cir.0000138928.83266.24
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial of Dalteparin for the Prevention of Venous Thromboembolism in Acutely Ill Medical Patients

Abstract: Background-Considerable variability exists in the use of pharmacological thromboprophylaxis among acutely ill medical patients, partly because clinically relevant end points have not been fully assessed in this population. We undertook an international, multicenter, randomized, double-blind, placebo-controlled trial using clinically important outcomes to assess the efficacy and safety of dalteparin in the prevention of venous thromboembolism in such patients. Methods and Results-Patients (nϭ3706) were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
649
1
53

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 876 publications
(719 citation statements)
references
References 27 publications
16
649
1
53
Order By: Relevance
“…The International Myeloma Working group and ASCO recommend prophylaxis with either aspirin or LMWH for lower risk patients, and LMWH for higher risk patients receiving thalidomide or lenalidomide. 47,61 Hospitalized patients Based on randomized clinical trials of thromboprophylaxis in medically ill hospitalized patients, 62,63 and a meta-analysis that demonstrated 40% lower rates of VTE with pharmacologic prophylaxis versus placebo, 64 the current ACCP 52 and ASCO guidelines 47 strongly recommend thromboprophylaxis in hospitalized medically ill and cancer patients, respectively. However, trials of thromboprophylaxis did not include HSCT patients who are not specifically included in these recommendations.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…The International Myeloma Working group and ASCO recommend prophylaxis with either aspirin or LMWH for lower risk patients, and LMWH for higher risk patients receiving thalidomide or lenalidomide. 47,61 Hospitalized patients Based on randomized clinical trials of thromboprophylaxis in medically ill hospitalized patients, 62,63 and a meta-analysis that demonstrated 40% lower rates of VTE with pharmacologic prophylaxis versus placebo, 64 the current ACCP 52 and ASCO guidelines 47 strongly recommend thromboprophylaxis in hospitalized medically ill and cancer patients, respectively. However, trials of thromboprophylaxis did not include HSCT patients who are not specifically included in these recommendations.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…Three large-scale prevention studies involving over 5,500 medically ill patients have shown that 11-15% and 4-5% of patients will have venous thromboembolism and proximal deep vein thrombosis, respectively, identified by screening studies in the absence of prophylaxis [3][4][5]. Additionally, the national DVT Free Registry found that 60% of patients diagnosed with an acute DVT were in the peri-hospitalization period.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical example of the underestimation of treatment effect by I-Fibrinogen scanning compared to venography has been shown by Rodgers [43]. Ultrasonography has been recently used in clinical trials but is not yet generalized for detecting asymptomatic DVTs without confirmatory venography [44].…”
Section: How Does the Performance Of An Imperfect Diagnostic Test Thmentioning
confidence: 99%